Strategies for writing argumentative academic essays - Moreno Tapia, Javier; Cáceres Mesa, Maritza Librada (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of this study was to recover the experience of a group of high school, undergraduate and postgraduate teachers who participated in a course focused on the promotion of reading comprehension skills and written composition of scientific texts, within which they had to appropriate a strategy to make a written composition putting into execution strategies of argumentation. For this, they answered a questionnaire at the end of the course where they pointed out the importance of applying specific actions of the socialized strategy before, during and after the process of composing argumentative texts.